A case of successfully resected Shamblin type III carotid body tumour without vascular reconstruction - Sreekumar, Surabhi; Raghunath, K. J.; Vijayalakshmi, S.; ., Sneha (International Surgery Journal, 2023)
Carotid body tumours (CBT) are rare vascular neoplasms arising from the bifurcation of the common carotid artery, and are benign tumors with low incidence, slow growth, and low rate for malignant transformation. A rare functional CBT may produce neuroendocrine secretions causing catecholamine-related symptoms, such as palpitations, headaches, hypertension, tachycardia, or flushing. These tumours have classic radiographic features. These lesions splay apart the internal (ICA) and external carotid arteries (ECA), and as it enlarges, it will encase, but not narrow the ICA and ECA-Lyre’s sign. If a diagnosis of CBT is suspected following a detailed physical examination, the diagnosis is almost always established by radiological imaging methods such as duplex ultrasonography, computed tomography (CT) angiography, magnetic resonance (MR) angiography, and digital subtraction angiography. These tumours were classified by Shamblin, according to the gross tumor vessel relationship and was based on the radiology, intraoperative findings and postoperative specimen examination. Group 1 tumors were minimally attached to the vessels and easily resectable. Group 2 tumors seemed to partially surround the vessel and were more adherent to vessel adventitia. These tumors were difficult to dissect but amenable to careful resection. Shamblin group 3 tumors had an intimate adherent relationship to the entire circumference of the carotid bifurcation and are usually inoperable. Surgical excision still remains the gold standard therapeutic modality for the treatment of CBTs. Radiotherapy is an alternative treatment modality which may decrease the tumor size or stop its growth. It is recommended for patients who cannot undergo surgery on account of extensive involvement, multiple tumors, and high operative and anesthetic risk.